ANALISIS KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR PERTAMBANGAN SEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2016 - Taghfirul Azhima Yoga S., S. Ko, Muhammad Noor Budi 1, Dr. Titin Ruliana, (EKONOMIA, 2021)
2018. Faculty of Economics, University August 17, 1945. Financial Performance in the Coal Sector Mining Sub-Sector company listed on the Indonesia Stock Exchange for the 2015-2016 Period, (under Supervisor I Mrs. Titin Ruliana and Supervisor II Mr. Taghfirul Azhima Yoga Siswa).The financial performance based on net profit margin ratio, return on assets, current ratio and quick ratio in the mining sector sub-sector of the coal sector in 2015-2016.The result of this based on profitability ratio analysis of the variable net profit margin (NPM) in the GEMS company (8,51%), ITMG (5,59%), KKGI (5,12%) and MYOH (0,25%). Likewise liquidity ratio in the current ratio (CR) variables in GEMS companies (97,99%), ITMG (45,50%), KKGI (183,14%), MBAP (137,57%) and PTBA (11,21%). And quick ratio (QR) variables in companies in GEMS companies (105,23%), ITMG (60,83%) KKGI (135,71%), MYOH (167,68%) and PTBA (9,64%). the financial performance decreased in 2016 on the variable return on assets (ROA) in MBAP companies (-8,45%), MYOH (-0,9%), PTBA (-1,16%) and TOBA (-3,53 %).The financial performance has increased in 2016 compared to 2015 against the variable net profit margin, current ratio and quick ratio. the variable return on assets (ROA) has decreased in 2016 compared to 2015